Pibid contributions for teachers continuous training of Pibid Unioeste Portuguese Subproject - Denise Raquel Zimmer; Greice da Silva Castela (Travessias, 2017)
This study aims to present the contributions of the Institutional Scholarship Program Introduction toTeaching (PIBID) for continuous training of supervisory teachers of Portuguese Language subproject of  PIBIDin the State University of Western Paraná (Unioeste). It is a guided research in Applied Linguistics, with the interview as na instrument used for the generation of data, which was recorded in audio with semistructured script. Four teachers of supervisory PIBID-Unioeste the Portuguese language subproject were the subjects of our research. In order tounder stand the characteristics, organization and objectives of the Program, we use official documents of CAPES and  MEC. Also, as our study covers, briefly, the historical overview about the training in Brazil, we base our research on the following authors: Candau (1999), Lima (2001), Libâneo, Oliveira, Toschi (2003), Costa-Hübes (2008). The results indicate that the Program objectives are being achieved, as the supervising teachers recognize how participation in PIBID assisted in continuous training, providing improvement in teaching practice.